RETRACTED: The Influence of Motivation, Compensation, And Work Environment on The Work Performance of Employees of The Noble Consumer Cooperative Majalaya Hospital - Gabriel Posenti Nggori Li; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the positive and significant influence on motivation, compensation, and work environment on employee performance. The research methodology used is quantitative method and uses multiple linear regression analysis with processing using Statistical Product and Service Solutions (SPSS) version 26 with data collection methods through questionnaires to 110 employees of the Koperasi Konsumen Mulia RSUD Majalaya. The results of this study indicate that there is an influence between Motivation (X1) and Employee Performance (Y) of 0.630 and has an influence of 63.0%. For the effect of the variable between Compensation (X2) and Employee Performance (Y) of 0.306 and has an effect of 30.6%. For the influence variable between the Work Environment (X3) and Employee Performance (Y) 0.441 and has an influence of 44.1%. The results showed that motivation, compensation, and work environment had a positive and significant impact on the employee performance of the Koperasi Konsumen Mulia RSUD Majalaya.